Transformasi Digital dalam Strategi Pemasaran PT. FASCO SAGA CORP: Studi pada Implementasi Media Sosial - Kharisma Nur Pribadi; Ika Purwanti (STIE AMKOP, 2025)
Introduction: The development of digital technology, especially social media, has opened up great opportunities for companies to optimize their marketing strategies. PT. Fasco Saga Corp, a building contractor company, faces challenges and opportunities in adopting digital transformation through social media marketing. This research aims to analyze the implementation of social media as a digital marketing strategy, the challenges faced, and its impact on marketing performance and the company's brand image. Method: The research method used is qualitative with interviews, participant observation, and documentation to collect data. Results: Digital transformation carried out by PT. Fasco Saga Corp is able to increase brand visibility and strengthen relationships with customers. The use of social media platforms such as Instagram, YouTube, TikTok, and Facebook can expand market reach and increase interaction with the audience. The main challenge faced by PT. Fasco Saga Corp is about maintaining content consistency, creative idea innovation, and digital advertising effectiveness. Conclusion: a well-planned digital marketing strategy can increase a company's competitiveness in an increasingly digital market.